Perancangan Gedung Olahraga Bulutangkis di Sport Center Sumatera Utara dengan Pendekatan Arsitektur Metafora - Rahadian Tri Syahputra; Suprayitno Suprayitno (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2023)
The aim of this article or writing is to obtain an international standard badminton sports building design in the North Sumatra sport center using a metaphorical architectural approach. The design is focused on predetermined themes covering architectural aspects, such as the arrangement of the sports arena and other supporting facilities. The study used in this design is the process of searching for ideas obtained through various sources of information regarding architectural data at the Badminton Sports Building and the metaphorical approach as a problem-solving material in which the realization of the design ideas is outlined in the form of images. This study concludes that in designing a badminton sports building, a form and design theme is needed that can stimulate people to come immediately because of their visual interest in the building. Therefore, the metaphorical architectural approach can support this as a limitation in the shape and design of this badminton sports building.